Rancang Bangun Aplikasi Mobile Kuliner (eMKUL) Menggunakan Location Based Service (LBS) Berbasis Android - Ramadhani Ramadhani; Benny Sukma Negara (UIN Sultan Syarif Kasim Riau, 2012)
Activity and mobility of human life is increasingly dense making information increasingly needed.One of the important information needs for humans is the need of food/culinary. Culinary informationincludes location information, menus, transactions, and route information (directions) the culinary.Location-based information services have an important role to help people solve those problems. Locationbased services (LBS) is a notion arising from the development of mobile technology, including technologydevelopment of Global Positioning System (GPS), Geographic Information Systems (GIS) and wirelesstelecommunication technologies (wireless).Mobile culinary (eMKUL) is the application uses location-based services to helppeople/communities to do culinary activity. Culinary activity mentioned is to search the culinary/restaurant,see the route/navigation, showing the position of the nearest culinary, culinary menus and makereservations. eMKUL applications built on the Android platform using the Java programming language.eMKUL application is client applications. This application requires an internet connection and GPS tomaximize use of existing features in eMKUL. eMKUL testing uses Black Box and User Acceptance Test.The test results provide the conclusion that all the features eMKUL can run well. eMKUL can help people /communities to access location-based culinary information.Keywords: Android, eMKUL, Location Based Service (LBS), Mobile Culinary